2002
DOI: 10.1067/mva.2002.119751
|View full text |Cite
|
Sign up to set email alerts
|

Durability of open repair of infrarenal abdominal aortic aneurysm: A 15-year follow-up study

Abstract: Open repair of infrarenal AAAs can achieve satisfactory 15-year follow-up rates of survival free from reintervention for any graft-related complications, suggesting that surgery should still be considered the procedure of choice for infrarenal AAAs, at least in patients who are fit for surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 24 publications
0
30
1
Order By: Relevance
“…Hallett reported a 9.4% graft-related complication rate (mostly anastomotic pseudoaneurysms) after open AAA repair at an average follow-up of 5.8 years with late surveillance imaging on most patients (Hallett et al, 1997). Finally, Biancari et al report of a 15.4% late graft-related complication rate with a median follow-up of 8 years (Biancari et al, 2002). This is significantly worse than the previous reports and may be related to the inclusion of ruptured AAA repairs.…”
Section: Incidence Of Anastomotic Aneurysmcontrasting
confidence: 48%
“…Hallett reported a 9.4% graft-related complication rate (mostly anastomotic pseudoaneurysms) after open AAA repair at an average follow-up of 5.8 years with late surveillance imaging on most patients (Hallett et al, 1997). Finally, Biancari et al report of a 15.4% late graft-related complication rate with a median follow-up of 8 years (Biancari et al, 2002). This is significantly worse than the previous reports and may be related to the inclusion of ruptured AAA repairs.…”
Section: Incidence Of Anastomotic Aneurysmcontrasting
confidence: 48%
“…A complication rate of 9.4%, especially in a patient such as ours, who was a poor candidate for surgery, has been reported [9,14,22].…”
Section: Discussionmentioning
confidence: 99%
“…Rupture of an AAA is a surgical emergency with a mortality rate, if untreated, of 90% at 6 weeks and an operative mortality rate of 30% to 60% [6][7][8][9]. In patients without hypertension [1,[10][11][12], a sealed aneurism could occur, without any significant change in blood values because of restricted blood loss.…”
Section: Discussionmentioning
confidence: 99%
“…Fontaine et al [18], observed aneurysm formation proximally to the prosthesis in 32% of patients 10.3 years after AAA repair. Biancari et al [19] found that in 15 year follow-up 12.5% of study group had any new aortic aneurysm and nearly 3% of all had TAAA. Thus, after open operation of AAA all patients must be under surveillance with at least periodic ultrasound examination.…”
Section: Discussionmentioning
confidence: 99%